An Analysis of SNAP Online Purchasing Behavior in California: A Review of the First 7 Months of Program Implementation and Lessons Learned - Foster, Isabelle S; LeBoa, Christopher; Hoffs, Charlie T; Polselli, Angelina M; de Nocker, Charly; Liu, Samantha Y; Rummo, Pasquale E; Brandt, Eric J; Rimm, Eric B (American journal of health promotion, 2023)
The Supplemental Nutrition Assistance Program (SNAP) Online Purchasing Pilot (OPP) allows for the online purchase of groceries using SNAP benefits. First implemented in California in late April 2020, little is known about program usage. This study assessed initial implementation of SNAP Online in California using SNAP OPP transaction data from April - October 2020. Insights can identify usage differences by demographics, store availability, and rurality to help inform future pilot programs and nutrition initiatives. Using generalized estimating equations, we modeled county-level associations between transactions and county-level demographics, rurality, and retailer availability. Transaction data from California's Department of Social Services (CDSS) was linked with publicly-available, county-level demographics. Anonymized county-level data on SNAP Online transactions and CalFresh households. The primary outcome was successful SNAP Online food transactions per county. Generalized estimating equation models with clustering by county was used. During the first 7 months, median SNAP Online transactions per county per month was 665; 2.7% of total SNAP redemptions were from SNAP Online. Counties with more female-led, disabled, Latino, or Asian CalFresh households had fewer Amazon transactions. Each additional Walmart per county corresponded to 260.7 more Walmart transactions (P < .001). Each percent increase in county zip codes covered by Amazon Fresh corresponded to 45.4 fewer Walmart transactions (P < .05) and 37.3 more Amazon transactions (P < .001). Number of stores per county was associated with greater online grocery transactions, whereas rurality was not. County-level SNAP demographics correlated with transactions at particular retailers.